2006
DOI: 10.1161/01.hyp.0000240332.01877.11
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Stroke by Home “Morning” Versus “Evening” Blood Pressure Values

Abstract: Abstract-Predictive power of self-measured blood pressure at home (home BP) for cardiovascular disease risk has been reported to be higher than casual-screening BP. However, the differential prognostic significance of home BP in the morning (morning BP) and in the evening (evening BP), respectively, has not been elucidated. In the Ohasama study, 1766 subjects (Ն40 years) were followed up for an average of 11 years. Key Words: self-measurement Ⅲ home blood pressure Ⅲ stroke Ⅲ general population Ⅲ morning-home b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(107 citation statements)
references
References 28 publications
2
104
0
1
Order By: Relevance
“…Again, this is in agreement with the Ohasama study, where morning and evening BP equally predicted the risk of stroke. 22 Interestingly, in the Ohasama study, subjects with morning but not evening BP elevation had similar risk of stroke as those with morning and evening BP elevation, whereas those with evening but not morning BP elevation had little difference from normotensives. 22 More importantly, the risk associated with morning hypertension was more pronounced in treated hypertensives.…”
Section: Morning Versus Evening Home Bpmentioning
confidence: 92%
“…Again, this is in agreement with the Ohasama study, where morning and evening BP equally predicted the risk of stroke. 22 Interestingly, in the Ohasama study, subjects with morning but not evening BP elevation had similar risk of stroke as those with morning and evening BP elevation, whereas those with evening but not morning BP elevation had little difference from normotensives. 22 More importantly, the risk associated with morning hypertension was more pronounced in treated hypertensives.…”
Section: Morning Versus Evening Home Bpmentioning
confidence: 92%
“…It has been reported that morning hypertension is a strong risk factor for stroke. 6,13 The difference between the morning and evening self-measured blood pressures is an independent determinant of cardiac dysfunction. 14 The potential cardiovascular advantages of controlling morning hypertension have not been fully demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…5 Several prospective studies that evaluated self-measured home blood pressure have indicated that morning hypertension, which includes the morning surge, is an important risk factor for stroke and cardiovascular events. 6 Antihypertensive medication is usually prescribed to be taken once in the morning to increase the likelihood of patient adherence. However, this medication schedule does not satisfactorily decrease morning hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…[123][124][125][126] However, home BP measured in the evening also has a high prognostic significance. 117,127 In contrast, there have been a number of reports from Western countries that home BP does not differ between the morning and evening, or that home BP is higher in the evening than in the morning. 128,129 This may be partly explained by the difference in evening BP measurement times (mostly early in the evening in Western countries, and before going to bed in Japan).…”
Section: Masked Hypertensionmentioning
confidence: 99%
“…Both patterns are considered to be possible risk factors of cardiovascular diseases. 109,110,[115][116][117][118] Home BP is usually measured two times a day, that is, in the morning and evening. According to reports from Japan, home BP is higher in the morning than in the evening.…”
Section: Masked Hypertensionmentioning
confidence: 99%